A metamaterial hepta‐band antenna for wireless applications with specific absorption rate reduction. Issue 10 (11th May 2019) - Saraswat, Ritesh K.; Kumar, Mithilesh
Abstract: Present article embodies the design and analysis of slotted circular shape metamaterial loaded multiband antenna for wireless applications with declination of SAR. The electrical dimension is 0.260 λ × 0.253 λ × 0.0059 λ (35 × 34 × 0.8 mm 3 ) of proposed design, at lower frequency of 2.23 GHz. The antenna consists of circular shape rectangular slot as the radiation element loaded with metamaterial split ring resonator (SRR) and two parallel rectangular stubs, etched rectangular single complementary split‐ring resonator (CSRR) and reclined T‐shaped slot as ground plane. Antenna achieves hepta bands for wireless standards WLAN (2.4/5.0/5.8 GHz), WiMAX (3.5 GHz), radio frequency identification (RFID) services (3.0 GHz), Upper X band (11.8 GHz—for space communication) and Lower KU band (13.1 GHz—for satellite communication systems operating band). Stable radiation patterns are observed for the operating bands with low cross polarization. The SRR is responsible for creating an additional resonating mode for wireless application as well as provide the declination in SAR about 13.3%. Experimental characteristic of antenna shows close agreement with those obtained by simulation of the proposed antenna.